PENGARUH PENAMBAHAN ATAP SEKUNDER KABIN MOBIL (SECONDARY CABIN ROOF) TERHADAP GAYA AERODINAMIS DAN 2) PERILAKU ARAH PADA MOBIL SEDAN - Suudi, Ahmad; Risano, A.Yudi Eka; Hakim, Andy Abdel (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
This paper describes aerodynamic tests (wind tunnel test) for a model of secondary cabin roof (SCR) applied in BMW M3 E92 Coupe. SCR is a vehicle accessory installed on vehicle roof useful to block heats from sun while the car parking. The test were conducted at UPT-Laboratorium Aero Gas Dinamika dan Getaran (LAGG)-BPPT, PUSPITEK, Serpong, to determine lift and drag coefficient (cl and cd) of vehicle. This model with scale of 1:4.5 was tested with rigid body made by wood. The SCR model has been made from aluminium and has two kinds of type, which are A and B. The model test was carried out with the following parameters: wind speed of 15, 20 m/s, then 1,5 cm and 2,5 cm for height of SCR from roof . Before the test start, the first things that must be done is preparation the tools for test, next step is calibration of external balance in wind tunnel to obtain matrix of calibration. The inverse of this matrix named matrix of test will be used as a multiply factor to voltage measurement from result test of external balance while test start. Output from this multiply is aerodynamic forces experienced by model test. Installing SCR made some change to aerodynamic experienced by vehicle. From data of test, installing SCR type B with height 1,5 cm rom roof, the smallest cl can be obtained for each variation of velocity are 0,3 for 15 m/s and 0,29 for 20 m/s. Meanwhile,  installing SCR type A with height 2,5 cm from roof, the smallest cd be obtained for each variation of velocity are 0,368 for 15 m/s and 0,355 for 20 m/s. This results are valid if only the flow regime of two corresponding fluid are same and with the same model too.  Keywords: SCR, Aerodinamics, Wind Tunnel.